Corporate Technological Competence and the Evolution of Technological Diversification - Fai, Felicia M. (Cheltenham: Edward Elgar Pub, 2003)
The author examines the persistence of corporate technological competencies and their gradual erosion through diversifying incremental change.
Includes bibliographic references (189-194) and index
uaj 24/03/2015
Loan
Keywords: Diversification in Industry; Technological Innovations; Technological Innovation - Management; Organisational Change